NUMERICAL CALCULATION OF CAVITATION BUCKETS FOR 2-D HYDROFOILS - Seber, Serdar; Ekinci, Serkan; Bal, Sakir (YILDIZ TECHNICAL UNIV, 2012)
In this study, the cavitation buckets for the two-dimensional hydrofoils are computed by using the boundary element methods. Dirichlet type potantial based boundary element methods (panel methods) used in the calculation and verification of cavitation buckets. With the help of a computer program (CDSM=Combined Doublet and Source Method) the hydrodynamic performance of sections was calculated in a systematic manner by changing the parameters affecting the cavitation. Design booklets and diagrams have been created based on these results. The diagrams of different variables are compared with each other. Angle of attack Minimum pressure coefficient (alpha-C-P), Angle of attack - Lift coefficient (alpha-C-L) using parameters have been presented in tables and diagrams. All data was collected in the booklets. By using this booklet it can be said where the cavitation is/isn't effective on the hydrofoil sections and which ranges on the booklets should be worked according to the analysis solutions. All results are discussed in a detailed manner.
Keywords: Cavitation; angle of attack; pressure coefficient; hydrofoil sections; boundary element method; FLOW; Engineering